Cross-border spatial development in Bavaria: Dynamics in cooperation - Potentials of integration - Tobias Chilla; Franziska Sielker (Verlag der ARL - Akademie für Raumentwicklung in der Leibniz-Gemeinschaft, 2022)
There are a number of reasons for considering the cross-border dimension of Bavaria's spatial development at the present time. First, there is a new awareness of cross-border development issues on the level of the federal state of Bavaria. This is particularly related to the border between Bavaria and the Czech Republic, which is so historically and politically complex that it has long been difficult to address on the Prague-Munich diplomatic level. Tangible developments have recently been seen here on the 'middle level'. At the same time the start of the macro-regional strategy EUSALP has led to increased discussion of spatial development instruments in the Alpine region. Second, the significance of borders was placed on the political agenda with unexpected force by the flows of refugees that largely began in 2015. After many years of widespread talk of a 'borderless' Europe, debates about refugee policies and border controls have made clear that the internal European borders still have considerable political significance. In Bavaria this mainly affects its border region with Austria. Third, a new impetus in cross-border cooperation on the European level can be identified: in recent years the focus was on activities in the immediate border area based on INTERREG-A and Euroregions. These remain important, but there is also a new impetus on the higher level, where macro-regions and numerous bilateral and multilateral forms of cooperation are creating new constellations. In Bavaria this can be seen particularly in the relatively new European Region of Danube-Vltava and through involvement in the Danube and Alpine macro-regions. Against this background, in 2015 the Bavarian Regional Working Group of the Academy for Spatial Research and Planning (Akademie für Raumforschung und Landesplanung, ARL) formed a subsection on cross-border spatial development in Bavaria. This large and exceptionally international group spent three years working on numerous facets of the topic at hand. Both the subsection and this publication aimed to find answers to the following questions: How are these current developments changing the constellations of actors and institutions in regional development and spatial planning? What is the significance of borders as spatial elements in the context of the dynamic developments? What are the opportunities and challenges presented by the new instruments and trends for planning and regional development practice?
urn:nbn:de:0156-415869; http://econpapers.repec.org/RePEc:zbw:arlaba:253341; http://econpapers.repec.org/RePEc:zbw:arlaba:253340; http://econpapers.repec.org/RePEc:zbw:arlaba:253339; http://econpapers.repec.org/RePEc:zbw:arlaba:253347; http://econpapers.repec.org/RePEc:zbw:arlaba:253344; http://econpapers.repec.org/RePEc:zbw:arlaba:253343; http://econpapers.repec.org/RePEc:zbw:arlaba:253342; http://econpapers.repec.org/RePEc:zbw:arlaba:253346; http://econpapers.repec.org/RePEc:zbw:arlaba:253345
Keywords: 710; borders; regional development; cross-border spatial planning; Alpine region; Austria; Czech Republic